USING QUILLBOT GRAMMAR CHECKER TO HELP STUDENTS WRITING SKILLS AT SMA 9 MUHAMMADIYAH MAKASSAR - Rasidin, Rayhan Hanif; Asrianto, Muhammad; Ariana (Journal of Language Testing and Assessment, 2025)
The objective in this research was to help students in writing with using quillbot grammar checker at SMA 9 Muhammadiyah Makassar in the academic years of 2022/2023.the study used quantitative research as its methodology. Pre-test and post-test about composing recount text were employed in this study. Students in the XI class at SMA 9 Muhammadiyah Makassar during the academic years 2022-2023 were focus of this study. In this study, samples were chosen at random, and the total population was 122 students, and the sample number was 24 students. The researcher used the writing test to gather quantitative information. The type of test was a recount text in which different topics are given to recount. The mean score of pre-test in the terms of students’ writing was 76, while in the post-test was 93, 4, and the improvement was 22, 89%.  It could be concluded that helping students’ writing shows that the using quillbot grammar checker improved the students’ writing, especially in terms of content, organization, vocabulary, language use, and mechanics. It indicated that there is significant improvement in students writing skills after being used quillbot grammar checker. Based on the result, quillbot grammar checker needed by students. It showed that using quillbot grammar checker was effective to help in learning process especially in writing. The researcher advised students to use any similar tools or website if it necessary but don’t forget to learn more about writing and always keep practice.